Modelagem conceitual DILAM: princípios descritivos de arquivos, bibliotecas e museus para o recurso imagético digital - Simionato, Ana Carolina [UNESP] (2015)
The airing of the images on social media and the Web are exponentials, provided by digital devices that are increasingly accessible. Therefore, the significant amount of shared resources is needed to capture imagery and its forms of dissemination by contemporary society. However, through this amount, procedures, the location and recovery of these expressions, are complicated tasks to the user by the variety of features described. Informational processes, such as the representation of information assist in intervention for retrieval of these records. In this sense, how to build a resource description is inclusive of imagery and admire the principles of archival, of librarianship and museology appraisal, the elements of the domain and the structure of the environment in the description of the characteristics of the resource? From the descriptive principles of three contexts and the digital environment, it is proposed to perform a theoretical study of descriptive treatment resource digital imagery in particular, in archives, libraries and museums, with an investigative approach in relation to integrative and divergent features among its descriptive principles. From the descriptive principles of three contexts and the digital environment, it is proposed to perform a theoretical study of descriptive treatment resource digital imagery in particular, in archives, libraries and museums, with an investigative approach in relation to integrative and divergent features among its descriptive principles.The overall objective is to propose a conceptual schema for the resource digital imagery that includes archives, libraries and museums, in domain, and environment focus. The research is classified as applied-theoretical and qualitative, in relation to development objective are in a conceptual modeling for registry informational integration. And exploratory, because the data collection from a bibliographic survey of national and international level in...